Mechanism of Action of Decitabine in the Treatment of Acute Myeloid Leukemia by Regulating LINC00599 - Fan Du; Ting Jin; Li Wang (Analytical Cellular Pathology)
Objective. Acute myeloid leukemia (AML) is a heterogeneous malignancy with a low long-term survival rate. The aim of this study was to investigate the effects of decitabine (DAC) treatment cell proliferation and apoptosis in AML and role of the expression of LINC00599 and, consequently, miR-135a-5p. Materials and Methods. Human promyelocytic leukemia cells (HL-60) and human acute lymphatic leukemia (CCRF-CEM) cells were treated with various concentrations of DAC. Cell proliferation in each group was detected using the cell counting kit 8. For each group, apoptosis and reactive oxygen species (ROS) levels were detected using flow cytometry. Reverse transcription polymerase chain reaction (RT-PCR) was performed to examine the expression of lncRNA LINC00599. The expression of apoptosis-related proteins was analyzed using western blotting. The regulatory relationship between miR-135a-5p and LINC00599 was verified by constructing miR-135a-5p mimics, miR-135a-5p inhibit, wild type LINC00599 3′-untranslated region (UTR), and mutant LINC00599 3′-UTR. Ki-67 expression in the tumor tissues of nude mice was detected using immunofluorescent assays. Results. Both DAC and LINC00599 Inhibit groups were able to significantly reduce the proliferation of HL60 and CCRF-CEM cells, increase apoptosis, upregulate the expression of Bad, cleaved caspase-3, and miR-135a-5p, downregulate the expression of Bcl-2, and elevate ROS levels in cells, with these effects being more pronounced after combined treatment with DAC and LINC00599 Inhibit. In comparison to mimic NC, the miR-135a-5p mimic group significantly decreased the relative fluorescence activity ratio of LINC00599 3′-UTR wild-type CCRF-CEM cells. The LINC00599 Inhibit and miR-135a-5p mimic groups exhibited substantially reduced proliferation of HL60 and CCRF-CEM cells, increased apoptosis, upregulated Bad, cleaved caspase-3, and miR-135a-5p expression, along with downregulated Bcl-2 and LINC00599 expression and increased ROS levels in cells; these effects were more pronounced after LINC00599 Inhibit was combined with miR-135a-5p mimics. In vivo experiments revealed that both DAC and LINC00599 Inhibit were able to considerably reduce the long diameter, short meridian, volume, and mass of tumors, increase miR-135a-5p expression, and decrease LINC00599 and ki-67 expression in tumor tissues of nude mice. This effect was more pronounced when the DAC and LINC00599 Inhibit were used in combination. Conclusion. DAC regulates the expression of miR-135a-5p by regulating the expression of LINC00599, which in turn affects cell proliferation, apoptosis, and tumor proliferation. Our findings provide a theoretical basis for improving the clinical outcome of AML.